COPING WITH SPORTS INJURIES AMONG INDIVIDUAL AND TEAM SPORT ATHLETES - Csukonyi, Csilla; Nagy, Réka (Stadium - Hungarian Journal of Sport Sciences, 2024)
In the study, we aimed to explore the differences between individual and team athletes due to their coping with sports injuries. The research consisted of qualitative and quantitative parts: one interview and two questionnaires were recorded. Due to our country’s rudimentary form of prevention and rehabilitation procedures for sports injuries, the study would show different results compared to a foreign sample. The practical benefit of the study lies in this, as the more information available about the differences in the psychological functioning of athletes, the more specific help can be provided to them during the activity of a sports psychologist.